Wage Mobility in the United States - Buchinsky, Moshe; Hunt, Jennifer (The Review of Economics and Statistics, 1999)
This paper examines the mobility of individuals through the wage and earnings distributions, using 1979-1991 data from the National Longitudinal Survey of Youth. Lifetime wages will be more equally distributed than wages from any single year if individuals change position in the wage distribution over time. The results suggest that mobility is predominantly within group mobility, reducing wage inequality by 12%-26% over a four-year horizon. A detailed examination of within-group mobility, using year-to-year estimates of transition probabilities among quintiles of the distribution, reveals similar general patterns across all skill groups: mobility declined significantly over the years, especially at the lower end of the wage and earnings distributions.